檔案評量於國中英語教學應用之個案研究 Applying a Portfolio Assessment of - 林素卿 Su-Ching Lin; 葉順宜 Shun-I Yeh (National Taiwan Normal University, 2014)
本研究旨在探討檔案評量於國中英語教學應用之情形，其目的在瞭解學生對檔案評量的看法與分析檔案評量對學生英語學習態度與成就之影響。本研究以七年級30 位學生為研究對象，設計10 個單元的檔案評量，進行為期12 週的研究，透過課堂觀察、訪談與師生對談、教師省思札記、文件分析、檔案評量回饋問卷、英語學習態度量表等方法蒐集資料。研究發現包括：一、學生對檔案評量持肯定的態度，認同檔案評量可提升自我之英文應用能力、自省及自主學習能力。二、檔案評量能提升學生的學習態度和學習成就。根據研究發現，本研究提出有關檔案的項目、學習單的設計、反省與回饋、評分方式與規準、評量人數等方面建議，作為實施檔案評量及未來研究之參考。 This study explored the effectiveness of applying a portfolio assessment to English teaching in a junior high school. The participants consisted of 30 seventh-grade students. Based on teaching units, the authors designed 10 unit assessment worksheets, and implemented them for 12 weeks. The objectives of this study were to investigate effective ways to apply the portfolio assessment to English teaching, to understand the attitudes and responses of students regarding the portfolio assessment, and to analyze the effects of the learning attitudes of students on their English learning performance. During the research period, the data were collected through classroom observations, teaching reflection journals, student worksheets, student learning reflections, interviews and teacher-student dialogues, documents, and questionnaires. Data analyses included both qualitative and quantitative methods. The results were as follows: (1) The students exhibited positive attitudes and responses regarding the portfolio assessment; they indicated that the portfolio assessment provided them with opportunities to apply English, and promoted their abilities of self-reflection and independent study; (2) The portfolio assessment enhanced the learning attitudes and performance of the students. Based on these findings, suggestions for teachers and future education researchers are provided in this paper.